2012
DOI: 10.1051/0004-6361/201117698
|View full text |Cite
|
Sign up to set email alerts
|

High cadence spectropolarimetry of moving magnetic features observed around a pore

Abstract: Context. Moving magnetic features (MMFs) are small-size magnetic elements that are seen to stream out from sunspots, generally during their decay phase. Several observational results presented in the literature suggest them to be closely related to magnetic filaments that extend from the penumbra of the parent spot. Nevertheless, few observations of MMFs streaming out from spots without penumbra have been reported. The literature still lacks analyses of the physical properties of these features. Aims. We inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
5
17
0
Order By: Relevance
“…Our transverse velocities compare well with studies of BPs around active regions. Most of these (Berger et al 1998;Möstl et al 2006;Criscuoli et al 2012) find mean horizontal velocities for BPs in active regions in the range 1-2 km s −1 , similar to those found here. It is also noteworthy that some observations (Berger et al 1998;Möstl et al 2006) find that BP velocities are attenuated in active regions compared to quiet Sun regions, as in the present work.…”
Section: Horizontal Velocity Properties and Lifetimessupporting
confidence: 84%
See 2 more Smart Citations
“…Our transverse velocities compare well with studies of BPs around active regions. Most of these (Berger et al 1998;Möstl et al 2006;Criscuoli et al 2012) find mean horizontal velocities for BPs in active regions in the range 1-2 km s −1 , similar to those found here. It is also noteworthy that some observations (Berger et al 1998;Möstl et al 2006) find that BP velocities are attenuated in active regions compared to quiet Sun regions, as in the present work.…”
Section: Horizontal Velocity Properties and Lifetimessupporting
confidence: 84%
“…Criscuoli et al (2012) find similar lifetimes for quiet Sun BPs in their study. It should be noted that Möstl et al (2006) report a mean lifetime of 263 ± 137 s for BPs observed in an active region which is longer than the value derived in the present study.…”
Section: Horizontal Velocity Properties and Lifetimessupporting
confidence: 79%
See 1 more Smart Citation
“…As a kind of basic magnetic elements on the Sun, MMFs play a key role in the decay phase of an AR (e.g., Criscuoli et al 2012). They are described as streaming out of sunspot penumbrae and moving toward the outer boundary of the moat regions.…”
Section: Introductionmentioning
confidence: 99%
“…The previous two types of MMFs have velocities of about 0.5−1 km s −1 , and the last one had speeds in the range of 2−3 km s −1 (Shine & Title 2001;Zhang et al 2007). It has been suggested that bipolar MMFs are the manifestations of Ω-shaped or U-shaped loops traveling along penumbral filaments, while unipolar MMFs are considered as the movement of single magnetic elements (Zhang et al 2003;Zuccarello et al 2009;Criscuoli et al 2012). According to Thomas et al (2002), MMFs should be the emerging effects of submerged penumbral flux tubes raised by convection.…”
Section: Introductionmentioning
confidence: 99%